Strongly promoting the foundational role and power of the people in the spirit of the 14th National Party Congress - TRẦN VĂN PHÒNG (Political Theory Journal, 2026)
The article analyzes and clarifies the requirements and tasks to strongly promote the foundational role and power of the people in the spirit of the 14th National Party Congress. It emphasizes deeply grasping the viewpoint of "the people as the root"; building and perfecting mechanisms and policies to effectively realize the people’s mastery; promoting the people’s mastery across all spheres of social life; urging cadres, party members, civil servants, and public employees to set examples in practicing democracy, complying with the law, and upholding responsibilities and social ethics; and promoting democracy together with strengthening social responsibility, order, and discipline.